2017
DOI: 10.1111/jsr.12616
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the upper airway in patients with quadriplegia and obstructive sleep apnea

Abstract: The aim of this study was to investigate upper airway anatomy in quadriplegics with obstructive sleep apnea. Fifty subjects were recruited from three hospitals in Australia: people with quadriplegia due to spinal cord injury and obstructive sleep apnea (n = 11), able-bodied people with obstructive sleep apnea (n = 18), and healthy, able-bodied controls (n = 19). All underwent 3-Tesla magnetic resonance imaging of their upper airway. A subgroup (n = 34) received a topical vasoconstrictor, phenylephrine and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…These include obesity (as indicated by increased specific measures of body habitus such as weight, body mass index (BMI), waist, abdominal, and neck girth) which is associated with OSA in both SCI24 and the general population 33. Obesity leads to narrowing of the upper airway by deposition in pharyngeal tissues including the tongue in both the general population and in SCI,22,34 in addition to the effect of reducing lung volume on decreased upper airway caliber during sleep 35. In chronic SCI, most authors have observed associations between OSA prevalence and increasing age, BMI and neck circumference,24,25,27,36 but these relationships appear weaker in the acute, post-injury period 23.…”
Section: Sleep-disordered Breathing In Scimentioning
confidence: 99%
“…These include obesity (as indicated by increased specific measures of body habitus such as weight, body mass index (BMI), waist, abdominal, and neck girth) which is associated with OSA in both SCI24 and the general population 33. Obesity leads to narrowing of the upper airway by deposition in pharyngeal tissues including the tongue in both the general population and in SCI,22,34 in addition to the effect of reducing lung volume on decreased upper airway caliber during sleep 35. In chronic SCI, most authors have observed associations between OSA prevalence and increasing age, BMI and neck circumference,24,25,27,36 but these relationships appear weaker in the acute, post-injury period 23.…”
Section: Sleep-disordered Breathing In Scimentioning
confidence: 99%
“…The pathogenesis of OSA results from a combination of anatomical and non-anatomical physiological traits including high upper airway collapsibility, low arousal threshold, high loop gain and low muscle responsiveness [9]. While the relative contributions of these factors are likely to be different in tetraplegia [10], anatomical and physiological changes associated with injury, such as altered autonomic [11], neuromuscular [12] and respiratory control [13], increased adipose tissue and neck circumference [2,14], and increased nasal resistance [15,16], may increase the risk of OSA in people with tetraplegia.…”
Section: Introductionmentioning
confidence: 99%
“…SDB, predominantly obstructive sleep apnoea (OSA), can be caused acutely by cervical spinal cord injury4–6 and is up to five times more prevalent in chronic quadriplegia7–16 compared with the general population 17 18. The pathophysiological basis for SDB remain unclear in quadriplegia,19 although both ‘spinal specific’ issues such as a higher nasal resistance,20 21 ventilatory control instability,22 23 altered upper airway reflex responses24 and an increased upper airway lateral wall size,25 coupled with a high rate of ‘general population’ risks in chronic quadriplegia such as obesity, ageing and a male predominance all contribute 14…”
Section: Introductionmentioning
confidence: 99%